The enhanced immunopharmacology of VIB4920, a novel Tn3 fusion protein and CD40L antagonist, and assessment of its safety profile in cynomolgus monkeys. (3rd February 2020) - Nicholson, Simone M.; Casey, Kerry A.; Gunsior, Michele; Drabic, Stacey; Iverson, William; Cook, Halie; Scott, Stephen; O'Day, Terry; Karanth, Subramanya; Dixit, Rakesh; Ryan, Patricia C.
Abstract : Background and Purpose: Inhibition of the T‐ and B‐cell interaction through the CD40/CD40 ligand (L) axis is a favourable approach for inflammatory disease treatment. Clinical studies of anti‐CD40L molecules in autoimmune diseases have met challenges because of thromboembolic events and adverse haemostasis. VIB4920 (formerly MEDI4920) is a novel CD40L antagonist and Tn3 fusion protein designed to prevent adverse haemostasis and immunopharmacology. We evaluated the pharmacokinetics, activity and toxicity of VIB4920 in monkeys. Experimental Approach: Cynomolgus monkeys received i.v. or s.c. 5–300 mg·kg −1 VIB4920 or vehicle, once weekly for 1 month (Studies 1 and 2) or 28 weeks (Study 3). VIB4920 exposure and bioavailability were determined using pharmacokinetic analyses, and immune cell population changes via flow cytometry. Pharmacological activity was evaluated by measuring the animals' capacity to elicit an immune response to keyhole limpet haemocyanin (KLH) and tetanus toxoid (TT). Key Results: VIB4920 demonstrated linear pharmacokinetics at multiple doses. Lymphocyte, monocyte, cytotoxic T‐cell and NK cell counts were not significantly different between treatment groups. B‐cell counts reduced dose‐dependently and the T‐cell dependent antibody response to KLH was suppressed by VIB4920 dose‐dependently. The recall response to TT was similar across treatment groups. No thromboembolic events or symptoms of immune system dysfunctionality were observed. Conclusions and Implications: VIB4920 demonstrated an acceptable safety profile in monkeys. VIB4920 showed favourable pharmacokinetics, dose‐dependent inhibition of a neoantigen‐specific immune response and no adverse effects on immune function following long‐term use. Our data support the use of VIB4920 in clinical trials.